2013
DOI: 10.1177/0218492312469803
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stress and coronary heart disease

Abstract: Our study found evidence of an independent causative association between psychological stress and coronary heart disease, of a similar order to the more conventional coronary heart disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…CHD has become the most common disease and the leading cause of death around the world [15]. It is well known that atherosclerosis is the main pathological basis of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…CHD has become the most common disease and the leading cause of death around the world [15]. It is well known that atherosclerosis is the main pathological basis of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies. 19,20-22 More than 96% of coronary patients suffer from moderate to severe stress. 19 in addition, prior cardiac disease, lifestyle components such as physical inactivity, smoking, alcohol drinking, abnormal BMI have an important role in increased risk of CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…19,20-22 More than 96% of coronary patients suffer from moderate to severe stress. 19 in addition, prior cardiac disease, lifestyle components such as physical inactivity, smoking, alcohol drinking, abnormal BMI have an important role in increased risk of CVDs. 20,21 Meanwhile, the results of a review study showed that bowel toxicity increases the risk of developing CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that physical activity can help manage stress (Manger & Motta, 2005; Nabkasorn et al, 2006; P. Salmon, 2001), and studies have linked chronic stress with certain health problems such as decline in verbal learning and memory (Agbenyikey et al, 2015), digestive diseases (Lee et al, 2015), and heart disease (Kurd et al, 2014). It is unclear whether the comparatively lower level of agreement that physical activity is done to help manage stress is because stress is less common than a desire to feel mentally and physically good today and to relieve physical and mental decline in the future or because the link between chronic stress and related health consequences is less understood.…”
Section: Discussionmentioning
confidence: 99%